Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1111/j.1479-828x.1996.tb03267.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Estimated Fetal Weight below 1,000g

Abstract: The Warsof formula is 1 of 3 currently recommended by the Australian Society for Ultrasound in Medicine for the routine estimation of fetal weight. However, this formula was derived using mostly large fetuses, and its accuracy in extremely low birth-weight fetuses is not known. Using this formula, we studied 184 infants delivering within 14 days of an estimated fetal weight (EFW) < 1,000 g. The mean percent error in EFW was 11.7% underestimation, with 80% of infants underestimated and 61% of estimates within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 7 publications
2
18
1
1
Order By: Relevance
“…However, the mean time interval was relatively short with 4.1 days. Surprisingly, Scott et al [8] who set the same maximum time interval of 14 days and had a mean time interval of 3.8 days found that the number of days between FWE and delivery were significantly associated with an error in FWE. While the mean percentage error at 9 days prior to delivery was 9.6%, it increased up to 32% when the FWE was done more than 9 days prior to delivery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the mean time interval was relatively short with 4.1 days. Surprisingly, Scott et al [8] who set the same maximum time interval of 14 days and had a mean time interval of 3.8 days found that the number of days between FWE and delivery were significantly associated with an error in FWE. While the mean percentage error at 9 days prior to delivery was 9.6%, it increased up to 32% when the FWE was done more than 9 days prior to delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies have analyzed the impact of GA on the accuracy of FWE [7,8,9]. While Heer et al [7] included neonates with a GA between 22 0/7 and 42 0/7 weeks, Mills et al [9] included only neonates with a GA between 22 0/7 and 28 6/7 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nossos dados também mostraram essa tendência a superestimar o peso fetal nos grupos de baixo peso (< 1000 g), e de subestimar no grupo de fetos macrossômicos (< 4000 g), em todas as fórmulas usadas, porém com resultados melhores com o uso das fórmulas de Hadlock. Já na detecção de fetos pesando menos de 1000 gramas, Scott et al (1996) relatam que a fórmula de Warsof (DBP e CA) apresenta um erro percentual médio de 11,7%, sendo que, em nosso estudo, com o uso dos parâmetros CA e CF, obtivemos um erro de 9,46%, e 70% dos casos apresentaram uma variação de até 10% do peso no nascimento, dado esse que reforça o achado por Guidetti et al (1990) que também preferem o uso desses parâmetros fetais na avaliação de fetos com restrição de crescimento.…”
Section: _______________________________________________________ Discunclassified